Kaplan Meier estimator on the survival of avocado (Persea americana) exporting companies in Peru, 2012-2020 - Pantaleón Santa María, Alberto Luis (2021)
The objective of this research was to apply the Kaplan Meier Estimator to determine the survival of avocado (Persea americana) exporting companies in Peru during 2012-2020. The results of the study showed that new companies are entering each year, with an entry rate of 33% for 2013 and 34% for 2020. The exit rate was 32% for 2013 and 29% for 2020. Likewise, it was found that the survival factor is decreasing as time goes by. The longer the time, the lower the chance of survival. Avocado exporting companies have a survival factor of 0,52 for the second year of life and 0,06 for nine years. This fact indicates that there is a high expectation of the companies to export avocado.